Penerapan Model Pembelajaran Tipe Learning Start a Question untuk Meningkatkan Keaktifan Belajar Sosiologi - Yetri Nomleni (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
The purpose of this study was to increase student activities in sociology learning with the Start A Question Type Learning Model. The type of research was classroom action research (PTK), which was conducted for two cycles, each covering four stages: planning, implementing, observing, and reflecting. The subjects of this study were students of Grade XI IPS II SMA Negeri Flobamorata Kupang, with a total of 23 students. Data analysis techniques used qualitative and quantitative analysis. Based on the results of the study, the application of the learning model Learning Start a Question can increase the student activities in sociology learning, with the results of the observation in cycle I of student activity being 70% and student test results with an average score of 71%. So, in Cycle I, the results of these observations and tests have not reached a level of success. This research continued to Cycle II with an average score of 80% and student test results 82%. Thus, it can be concluded that applying the learning model Type Learning Start a Questions can increase the activeness of teaching sociology for Grade XI IPS SMA Kebangakan Ekspor Flobamorata Kupang.